The Role of Corporate Social Responsibility, Good Corporate Governance, and Financial Performance on Firm Value in the Indonesian Banking Industry - Berry, Yunike; Fathimah, Charmelia (AIBPM Publisher, 2024)
Indonesian Banking Industry is one of the industries that remains strong in supporting national economic recovery during the Covid-19 pandemic. The firm value of banks in Indonesia has fluctuated during this period. The firm value can increase if it carries out Corporate Social Responsibility (CSR), in addition, good corporate governance (GCG) will encourage companies to manage professionally. This research aims to reexamine the influence of CSR, GCG, and financial performance on firm value listed on the Indonesia Stock Exchange in the banking sector. The method used in this research is a panel data regression analysis using secondary data obtained from financial statements and sustainability reports of banking companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The conclusion shows that financial performance variables with the Return on Assets (ROA) indicator significantly influence the company's value. Meanwhile, CSR and GCG do not significantly influence firm value. The results of this research indicate that although ROE is an important financial performance indicator, investors may pay more attention to other indicators that are considered more relevant in determining company value, such as Return on Assets (ROA).